HOW CAN HALAL CERTIFICATION SERVICES ADVANCE TOWARD DIGITAL MATURITY? A PUBLIC INNOVATION PERSPECTIVE - Yeti Rohayati; Tati Sarihati; Shinta Dzauharoh (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
Halal certification services for MSMEs have become increasingly important amid the strengthening of halal certification obligations, the acceleration of public service digitalization, and the growing demand for services that are simpler, faster, and more responsive. This condition creates an urgent need to examine the extent to which halal certification services have progressed toward digital maturity from a public innovation perspective. This study aims to analyze the movement of halal certification services for MSMEs toward digital maturity by focusing on process integration, ease of access, quality of assistance, and user orientation. The theoretical framework draws on public innovation, public service quality, and digital maturity. This study employs a qualitative approach with a case study design based on document analysis and secondary data, using documentation techniques, purposive sampling, and thematic analysis. The findings show that halal certification services have been digitalized and institutionally strengthened, yet their level of maturity remains developing because process integration, service standardization, and user experience have not been fully consistent. These findings indicate that digital transformation in service delivery requires institutional capacity, not merely the existence of digital platforms